Screening of Health-Associated Oral Bacteria for Anticancer Properties in vitro - Baraniya, Divyashri; Jain, Vinay; Lucarelli, Ronald; Tam, Vincent; Vanderveer, Lisa; Puri, Sumant; Yang, Maobin; Al-hebshi, Nezar Noor (Frontiers in Cellular and Infection Microbiology, 2020)
While extensive literature exists about the role of oral bacterial pathogens like Porphyromonas gingivalis and Fusobacterium nucleatum in oral squamous cell carcinoma (OSCC), the role of health-associated species has been largely unexplored. In this study, we assessed the effect of Streptococcus mitis, Rothia mucilaginosa, Neisseria flavescens, Haemophilus parainfluenzae, Lautropia mirabilis and Veillonella parvula on proliferation and expression of marker genes (IL-6, TNF-α, MMP3, CD36, CCD1 and NANOG) in OSCC cell lines CAL27, SCC25 and SCC4. Porphyromonas gingivalis was included as a pathogenic control. Both bacterial lysates (3 concentrations) and live cells (3 MOIs) were tested. S. mitis, H. parainfluenzae and N. flavescens resulted in substantial, dose-dependent reduction of proliferation, which was found to be mediated by H2O2 for the former and intracellular infection in the latter two species. However, only H. parainfluenzae showed differential antiproliferative effect against the cancer cell lines versus the normal control (TIGKs). In the gene expression assays, the health-associated species mostly downregulated CD36, a gene that plays an important role in tumor growth and metastasis, while P. gingivalis upregulated it. IL6 and TNF expression, on the other hand, were upregulated by almost all species, particularly the Gram-negatives including P. gingivalis. The effect on other genes was less evident and varied significantly by cell line. This exploratory study is the first insight into how health-associated bacteria may interact with OSCC. Further studies to explore whether the observed effects may have implications for the prevention or treatment of oral cancer is warranted.